High resolution analysis of snake venom metalloproteinase (SVMP) peptide bond cleavage specificity using proteome based peptide libraries and mass spectrometry - Paes Leme, Adriana F. (2011)
Both serine and metalloproteinases have been shown to play the role of toxins in the venoms of many snakes. Determination of the natural protein substrates of these toxins is an important feature in the toxinological characterization of these proteinases. Furthermore, characterization of their peptide bond specificity is of value for understanding active site preference of the proteinase associated with effective proteolysis as well as of use in the design of peptide substrates and inhibitor lead compounds. Typically the determination of peptide bond cleavage specificity of snake venom serine proteinases (SVSPs) and snake venom metalloproteinases (SVMPs) has been performed using limited sets of peptides or small oligopeptides as experimental substrates. Although this approach has yielded valuable data it is generally limited in scope due to the relatively small sets of substrates used to generate the consensus specificity sequences for these proteinases. In this study we use a large, plasma based, proteome-derived peptide library as substrates along with mass spectrometry to explore the peptide bond specificity of three PI SVMPs and one PIII SVMP to determine their individual peptide cleavage consensus sequences. All of the proteinases assayed displayed a clear preference for a leucine residue in the P1′ site. Careful analysis of the specificity profiles of the SVMPs examined showed interesting differences in the preferences at the other P and P′ sites suggesting functional differences between these proteinases. The PI SVMPs, leucurolysin-a, atrolysin C, and BaP1, showed preferences across the full P4 to P4′ range whereas the PIII SVMP bothropasin showed a narrower range of preferences across the sites. In silico docking experiments with the experimentally derived consensus sequences as well as with comparison of the results to those in the literature regarding peptide bond specificity based on both peptide and protein substrates give rise to a fresh understanding of the specificity of these SVMPS and may serve as a foundation for future experiments to better elucidate their mechanism of action in the complex pathophysiology of snakebite envenomation.